2007
DOI: 10.1021/om060641o
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Dinuclear Vinylidene Complexes and Their New Deprotonation Reactions

Abstract: The dinuclear dicationic vinylidene complex {[Ru]dCdC(Ph)CH 2 C(CH 2 CN)dCd[Ru]} 2+ (7a, [Ru] ) Cp(PEt 3 ) 2 Ru) is prepared from the reaction of ICH 2 CN with {[Ru]dCdC(Ph)CH 2 CtC[Ru]} + (6a). Deprotonation of 7a by n-Bu 4 NOH is followed by a cyclization process yielding the stable complex 9a, containing a five-membered carbocyclic ring ligand, which is fully characterized by 2D-NMR analysis and a single-crystal X-ray diffraction analysis. Similarly deprotonation of {[Ru]dCdC(Ph)CH 2 C(CH 2 -COOEt)dCd[Ru]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 100 publications
2
13
0
Order By: Relevance
“…We have described the preparation of osmium borylvinylidene derivatives through a 1,3-boryl shift in alkynyl boryl intermediates . Dicarbon-disubstituted vinylidenes are generally salts, which have been prepared by electrophilic addition to the C β atom of an alkynyl ligand . Under appropriate conditions, it is also possible to form dicarbon-disubstituted vinylidenes starting from unfunctionalized internal alkynes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have described the preparation of osmium borylvinylidene derivatives through a 1,3-boryl shift in alkynyl boryl intermediates . Dicarbon-disubstituted vinylidenes are generally salts, which have been prepared by electrophilic addition to the C β atom of an alkynyl ligand . Under appropriate conditions, it is also possible to form dicarbon-disubstituted vinylidenes starting from unfunctionalized internal alkynes .…”
Section: Resultsmentioning
confidence: 99%
“…In the 13 C{ 1 H} NMR spectrum the alkylidyne C(1) atom displays a triplet ( 2 J C−P = 11.4 Hz) at 267.1 ppm. As expected for equivalent phosphines, the 31 P{ 1 H} NMR spectrum shows a singlet at 23.7 ppm. An extended view of the structure (Figure 4) reveals that, like those of 2, the molecules of this complex form infinite chains, in this case by means of intermolecular N−H•••Cl(2) hydrogen bonds (chlorine trans to hydride).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[5] The known dicarbon-disubstituted vinylidenes have been generally prepared by electrophilic addition to neutral alkynyl complexes. [6] Ishii and coworkers have demonstrated that under appropriate conditions it is also possible to form dicarbon-disubstituted vinylidenes from unfunctionalized internal alkynes. [7] Both allenes and alkylidenecyclopropanes have been used to prepare ruthenium [8] and osmium vinylidenes, [9] respectively.…”
mentioning
confidence: 99%
“…They also reported that terminal alkynals are useful substrates for generating such vinylidene complexes which are easily prepared by dehydrative cyclization of these terminal alkynals in the presence of several transition‐metal compounds in a single step ,. And we have reported that the nucleophilic addition of propargyl Grignard reagents to Cγ of an allenylidene ligand and subsequent cyclization of the resulting diyne catalyzed by gold complex yielded a vinylidene with the Cβ incorporated into a five‐membered ring ,. Reported in this paper, vinylidene complexes 5 , 8 , 13 or 23 with the Cβ integrated into a ring structure are readily prepared in high yield.…”
Section: Resultsmentioning
confidence: 78%